Dendritic Branching of Retinal Ganglion Cells as a Biomarker of Glaucomatous Optic Neuropathy and Alzheimer’s Disease and a Target of Neuroprotective Therapy - M. V. Zueva; A. N. Zhuravleva; A. N. Bogolepova (Oftalʹmologiâ)
Irreversible damage to the structure of axons and death of the retinal ganglion cell (RGC) soma in primary open-angle glaucoma (POAG) and Alzheimer’s disease (AD) develop against the background of the already existing clinical manifestation, which is preceded by a slow period of progressive loss of synapses and dendrites of the RGCs. Recent studies have shown that the integrity of the RGC’s dendritic branching can serve as both a target of neuroprotective therapy and a sensitive marker of retinal degeneration in AD and glaucoma. To develop methods of complex neuroprotective therapy, it is necessary to substantiate the targets and tactics of affecting the dendritic tree of the RGCs, the remodeling of which, according to modern concepts, can be closely and antagonistically related to the regeneration of the axon after its damage in trauma and neurodegenerative diseases. RGCs are highly capable of functional modification. Currently, it has been proven that the use of neuroprotective drugs and neurotrophins is promising for maintaining the adaptive plasticity of RGCs and restoring their synaptic contacts at the level of the retina and brain. Understanding the features of the adaptive plasticity of RGCs in AD and glaucoma will make it possible to use technologies to activate the internal potential of neuronal remodeling, including the modification of dendritic branching of RGCs and regeneration of their axons, in the preclinical stages of these diseases. Increasing knowledge about the sequence and mechanisms of early events in the retina’s inner plexiform layer will contribute to the development of targeted neuroprotective therapy and new technologies to detect early POAG, AD, and, possibly, other systemic and local neurodegenerative conditions.